'Inflammatory breast cancer' due to metastatic adenocarcinoma of lung. (1st September 2016) - Ninan, Jacob; Naik, Vinay; George, Gemy Maria
Abstract : A 67-year-old woman with a history of lung adenocarcinoma presented with 3 weeks of redness, pain, swelling and skin changes in her right breast. Her vital signs and physical examination were within physiological limits except for the right breast. She had extensive red streaks radiating from the right nipple with peau d'orange appearance of her overlying skin. Her breast was tender on examination and did not have any associated cervical or axillary lymphadenopathy. Her mammography revealed thickening of the skin, increased parenchymal markings and shrinkage the breast. Multiple skin biopsies demonstrated moderately differentiated lung adenocarcinoma with lymphovascular invasion. The patient made an informed decision to undergo radiotherapy following discussion with her oncologist and breast surgeon. She succumbed to her illness 2 months after the diagnosis of metastasis to her breast.